Kalaimakaḷ poṉviḻāk katampam, 1932-1981 : poṉviḻā veḷiyīṭu (Kalaimakaḷ Kāriyālayam, 1982)
Golden jubilee volume of Kalaimakal, Tamil monthly; comprises a selection of short stories, poems, plays, and essays from the journal.